Digitization of taxes in Poland and its impact on the accounting information system: A Literature Review - Marzena RYDZEWSKA; Iwona MAJCHRZAK (Communications of International Proceedings, 2025)
The aim of this article is to review digital tools implemented in the area of tax settlements and tax reporting that have an impact on the accounting information system of enterprises in Poland, as well as to identify the challenges and benefits that digitisation in taxation brings to enterprises and accountants. Currently, there are few studies in the literature that address the impact of digitisation and digital transformation in the field of taxation on the organisation of accounting. The research undertaken aims to fill this gap. In the course of the research, a literature review was conducted, covering the issues of tax digitisation in Poland. An analysis of legal regulations obliging entrepreneurs to use specific digital tools was also carried out. The research used methods of analysis and criticism of sources. The results of the research indicate that the implementation of new digital solutions in the area of taxation enables the tax administration to access tax data more quickly, streamlines the processes of their analysis and improves the effectiveness of tax enforcement. The digitisation of taxes also has a direct impact on the functioning of accounting in enterprises. It brings about changes in its organisation and increases the costs associated with fulfilling new obligations regarding the generation of tax data in the required form. The use of new digital tools also requires the improvement of professional skills of accountants and allows for the automation of tax activities, which in turn leads to time savings and minimises the risk of mistakes.
Keywords: digitization; tax digitization; digitization in accounting.